LINE AS AN EXPRESSIVE MEANS IN DESIGNOF THE VISUAL ENVIRONMENT - Kolisnyk, O. V.; Pashukova, S. G.; Chernova, P. S. (Art and Design, 2021)
The purpose. The peculiarities of the use of linear images in the visual environment are investigated. Their influence on human perception and relevance of their use in design and art is determined. Methodology. General scientific research methods are used: analytical, typological, comparative analysis are used to determine the lines and their application in advertising and design. Results.Linear images differ against the background of modern media space. The use of linear, schematic, simplified images and their assimilation appeals to the historical development of human perception, which allows such images to be perceived on a subconscious level, without requiring concentration and distraction from other activities. Trends in the development of linear images in human perception are analyzed. The use of lines in various types of fine arts is emphasized and revealed. The scientific novelty. To consider the lines as a tool for visual emphasis of facilities and distribution lines in various forms of art. Their historical development and significance for human activity are established. Practical significance. The study allows to expand knowledge about the use of lines in modern and elite areas of art. The obtained results can be used in further studies of linear visual solutions.